Endoscopic vacuum therapy in the upper gastrointestinal tract - Kirsten Boonstra; Lisanne M. D. Pattynama; Lisanne M. D. Pattynama; Lisanne M. D. Pattynama; Lisanne M. D. Pattynama; Yasmijn J. van Herwaarden; Wietse J. Eshuis; Wietse J. Eshuis; Roos E. Pouw; Roos E. Pouw; Roos E. Pouw (Frontiers in Gastroenterology)
Endoscopic vacuum therapy (EVT) is a promising and versatile intervention for managing transmural defects in the upper gastrointestinal tract. Despite challenges, EVT exhibits great efficacy and safety, emphasizing the need for standardized protocols and evidence-based practices. We provide an overview, including mechanism, indications, types of EVT devices and complications, guiding clinicians in decision-making. Common challenges in EVT are highlighted, facilitating adequate implementation of EVT and helping to avoid common mistakes in daily practice.